2018
DOI: 10.1016/j.celrep.2018.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Entry, Replication, Immune Evasion, and Neurotoxicity of Synthetically Engineered Bat-Borne Mumps Virus

Abstract: Highlights d Bat mumps virus can readily replicate in human cells d Host cell entry factors of bat mumps virus are identical to those of human viruses d Bat mumps virus can evade innate immune responses in human and in bat cells d Neurotoxic properties of bat mumps virus are comparable to human field isolates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Interestingly, the absence of EPs 7630-induced antiviral activity against mumps virus supports the previous finding on measles virus ( Michaelis et al, 2011 ) but contrasts inhibition of respiratory syncytial virus (RSV). Whereas measles and mumps virus mainly use CD150 and CD46 (measles virus) ( Hashimoto et al, 2002 ), or sialic acids and glycan motifs (mumps virus) ( Kubota et al, 2016 ; Kruger et al, 2018 ; Kubota et al, 2019 ) for entry, RSV was shown to use distinct cell surface molecules, including glycosaminoglycans (GAG), intercellular adhesion molecule 1 (ICAM-1), and epidermal growth factor receptor (EGFR) ( Battles and McLellan, 2019 ). Previous studies suggested that flavonoids inhibit GAG synthesis ( Moskot et al, 2015 ; Qiu et al, 2017 ), block ICAM-1 induction ( Chen et al, 2004 ; Owens et al, 2009 ), and inhibit EGFR ( Firdous et al, 2014 ; Shah and Seth, 2021 ), potentially explaining the differential antiviral activity of EPs 7630 against RSV and the two paramyxoviruses measles and mumps virus.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the absence of EPs 7630-induced antiviral activity against mumps virus supports the previous finding on measles virus ( Michaelis et al, 2011 ) but contrasts inhibition of respiratory syncytial virus (RSV). Whereas measles and mumps virus mainly use CD150 and CD46 (measles virus) ( Hashimoto et al, 2002 ), or sialic acids and glycan motifs (mumps virus) ( Kubota et al, 2016 ; Kruger et al, 2018 ; Kubota et al, 2019 ) for entry, RSV was shown to use distinct cell surface molecules, including glycosaminoglycans (GAG), intercellular adhesion molecule 1 (ICAM-1), and epidermal growth factor receptor (EGFR) ( Battles and McLellan, 2019 ). Previous studies suggested that flavonoids inhibit GAG synthesis ( Moskot et al, 2015 ; Qiu et al, 2017 ), block ICAM-1 induction ( Chen et al, 2004 ; Owens et al, 2009 ), and inhibit EGFR ( Firdous et al, 2014 ; Shah and Seth, 2021 ), potentially explaining the differential antiviral activity of EPs 7630 against RSV and the two paramyxoviruses measles and mumps virus.…”
Section: Discussionmentioning
confidence: 99%
“…Very effective furin inhibitors containing a C-terminal 4-amidinobenzylamide residue have been developed in recent years. Several of these analogs have been successfully used to inhibit the replication of numerous furin dependent human pathogenic viruses such as H5N1 influenza A virus, Chikungunya virus, West Nile virus and dengue-2 virus, mumps virus or respiratory syncytial virus (reviewed in references 49 , 55 , and 56 ). So far, these inhibitors have been used only in virus-infected cell cultures and not in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Very effective furin inhibitors containing a C-terminal 4-amidinobenzylamide residue have been developed in recent years. Several of these analogues have been successfully used to inhibit the replication of numerous furin dependent human pathogenic viruses like H5N1 influenza A virus, Chikungunya virus, West-Nile virus and Dengue-2 virus, Mumps virus or respiratory syncytial virus (RSV) (reviewed in Steinmetzer and Hardes, 2018; Krüger et al, 2018; Van Lam van et al, 2019). So far, these inhibitors have only been used in virus infected cell cultures, but not in animal models.…”
Section: Discussionmentioning
confidence: 99%